Design of a 3-DOF prosthetic wrist for low-cost transradial myoelectric upper limb prosthesis - Narvaez D. (2019)
This paper presents the design of a 3-DOF prosthetic wrist for transradial myoelectric upper limb prosthesis that allows the orientation of a prosthetic hand to reduce compensatory movements that cause musculoskeletal problems mainly in the back and shoulder. The device is capable of perform passively abduction-adduction movements and actively flexion-extension and pronation-supination movements. The system has a DC motor that transmits power to the active movements and a solenoid for the choice of the type of movement to be performed. In order to validate the design of the components of the device, calculations and simulations were carried out by finite elements method to determine deformations, mechanical resistance and fatigue to define the critical components and maintenance periods. © 2019 IEEE.